Prophet Muhammad oblivion’s incidence and significance A Case study of Hadith - Samer Najeh Samarh (Global Journal Al-Thaqafah, 2017)
This paper reviews oblivion cases have happened in HADITH. Many related HADITH are collected and analyzed in order to understand it and consequently conclude oblivion issue advantages and significance. However, in this research oblivion definition and its derivatives are reviewed. Moreover, collected HADITH are reviewed supposing that Prophet Mohammad is an ideal messenger of God’s Quotes as well as a person who has a mutual properties with normal people. In addition, scientists’ guests regarding oblivion issue are collected and analyzed so as to come out with optimum results. Finally, the advantages of oblivion cases in HADITH and its significance on nations are highlighted.